2004
DOI: 10.1515/sg-2004-0001
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Heterosis: Effects of Hardy-Weinberg Disequilibrium

Abstract: SummaryThe mechanistic explanation of heterosis has been traditionally based on quantitative differences of gene effects. However, for outcrossing populations, heterosis is also a property of populations. In this paper, the effects of the deviation of a population from Hardy-Weinberg equilibrium (HWE) on the magnitude of heterosis have been examined numerically. The mating of two populations in HWE may generate directions and magnitudes of heterosis different from the mating of two populations in Hardy-Weinber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Based on the chi-square test, it was shown that four of six SNPs, including g.15284 C>T, g.15525 G>A, g.15853 G>A, and g.15905 G>A were in Hardy-Weinberg equilibrium (P>0.05) in Bali cattle, while in Belgian Blue, Limousine, Wagyu and PO populations could not be counted because it was monomorphic. The disequilibrium of SNP polymorphism is caused by three factors, and they are non-random mating, mutation, and selection in the population (Wu et al, 2004).…”
Section: Allele and Genotype Frequencies And Chi-square Test Of Snp 3...mentioning
confidence: 99%
“…Based on the chi-square test, it was shown that four of six SNPs, including g.15284 C>T, g.15525 G>A, g.15853 G>A, and g.15905 G>A were in Hardy-Weinberg equilibrium (P>0.05) in Bali cattle, while in Belgian Blue, Limousine, Wagyu and PO populations could not be counted because it was monomorphic. The disequilibrium of SNP polymorphism is caused by three factors, and they are non-random mating, mutation, and selection in the population (Wu et al, 2004).…”
Section: Allele and Genotype Frequencies And Chi-square Test Of Snp 3...mentioning
confidence: 99%
“…However, the long growth cycle of forest tree is the main problem, so shortening the breeding cycle is always the focus of forest tree breeding program. A lot of research on the theory and method for the early selection in many species were carried on [3][4][5][6]. On the basis of the law of tree growth and development, correlation between early and late stages of growth, and the effective age of early selection and selection trait can be find out.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this theoretical population would have genotype and gene frequencies which are at an equilibrium and will continue this way indefinitely provided the assumptions are met. However, it is clear that these assumptions do not hold for many species, and thus this equation serves as a way to determine the degree to which a population deviates from equilibrium (Wu et al, 2004;Dharmarajan et al, 2013).…”
Section: List Of Tablesmentioning
confidence: 99%